Revisión sistemática: efecto del mindfulness en el contexto escolar (2020)
This document presents the obtained data through a systematic analysis from the globally articles about Mindfulness between 2011 and 2019. The data has been extracted from the most scientifically recognized database, such as SciELo, Redalyc, Google Academic and Dialnet. Thus, the number of founded articles are nineteen articles. We have analyzed the categories of them: information data, investigation proposals, methodological aspects and final results. As well as the title of the articles, authors, countries, database, keywords, goals, types of investigations, population, populations age and the findings of each article plus its own conclusions. The results show that in most of the articles denoted the effects of Mindfulness practice in educational context, likewise exist studies which didn't find evidence of the practice.